Humoristic and naturalistic features in Charles Frazier's Cold Mountain - Taberyová, Jitka (2006)
This B.A. thesis deals with humoristic and naturalistic features in the novel "Cold Mountain" written by the contemporary American writer Charles Frazier. Several types and roles of naturalistic descriptions and humor that occur in the novel are listed and examined in the thesis, especially the function of such features and descriptions in the context. The possible impact of humoristic and naturalistic descriptions on the reader is suggested in the thesis, too.